2021
DOI: 10.1186/s12913-021-06246-1
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous melanoma: cost of illness under Brazilian health system perspectives

Abstract: Background The landscape of cutaneous melanoma (CM) diagnosis, staging, prognosis, and treatment has undergone fundamental changes in the past decade. While the benefits of new health resources are recognized, there is a distinct lack of accurate cost-of-illness information to aid healthcare decision makers. Methods The cost-of-illness study for CM was conducted from the perspective of two health systems in Brazil: the public health system (Unified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…They have analysed the cost-drivers at two levels - executional and structural. While the executional cost-drivers are relevant for deciding short term tactics to improve process efficiency, the structural cost-drivers relate to long-term and strategic issues in the larger system or value-chain [ 23 ]. In the current study, the patient volume in relation to human resources was an executional cost-driver in public facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have analysed the cost-drivers at two levels - executional and structural. While the executional cost-drivers are relevant for deciding short term tactics to improve process efficiency, the structural cost-drivers relate to long-term and strategic issues in the larger system or value-chain [ 23 ]. In the current study, the patient volume in relation to human resources was an executional cost-driver in public facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in India and other LMICs have found that public sector tends to under-provide certain services because of being under-funded [ 23 , 57 ]. In the current study, government spent a very small amount on providing diagnostics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma is a major cause of cancer death in the USA and worldwide (American Cancer Society, 2022). Melanomas detected at earlier stages have substantially better survival rates and lower associated costs of care, (Alexandrescu, 2009;Bencina et al, 2017;Buja et al, 2018;da Veiga et al, 2021;Dranitsaris et al, 2018;Elliott et al, 2017;Gogebakan et al, 2021;Keung & Gershenwald, 2018;Leeneman et al, 2021;Lyth et al, 2016;Serra-Arbeloa et al, 2017;Tsao et al, 1998) but general-population-based screening for melanoma has been controversial (Kulkarni et al, 2022;Swerlick, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma is a major cause of cancer death in the USA and worldwide (American Cancer Society, 2022). Melanomas detected at earlier stages have substantially better survival rates and lower associated costs of care, (Alexandrescu, 2009; Bencina et al, 2017; Buja et al, 2018; da Veiga et al, 2021; Dranitsaris et al, 2018; Elliott et al, 2017; Gogebakan et al, 2021; Keung & Gershenwald, 2018; Leeneman et al, 2021; Lyth et al, 2016; Serra‐Arbeloa et al, 2017; Tsao et al, 1998) but general‐population–based screening for melanoma has been controversial (Kulkarni et al, 2022; Swerlick, 2022). For example, although the vast majority of melanomas are readily observable on the skin, the value of provider‐based melanoma screening has been challenged, (Janda et al, 2020; Welch et al, 2021) and the United States Preventive Services Task Force has concluded that there is insufficient evidence to support general population screening in asymptomatic adults (US Preventive Services Task Force, 2016).…”
Section: Introductionmentioning
confidence: 99%